Briefe eines Intellektuellen 1886–1937 : Hrsg. von Thomas Kroll / Friedrich Lenger / Michael Schellenberger - Sombart, Werner 1863-1941 (Deutsche Geschichtsquellen des 19. und 20. Jahrhunderts, 2019)
The select correspondance of Werner Sombart (1863–1941), edited in this volume, shows a leading economist and sociologist of Imperial and Weimar Germany at work and documents his changing scholarly and political thinking. His letters unfold a wide-ranging intellectual network comprising politicians of varying persuasions, scholars, poets and renowned publishers